An Intervention Design: Supporting Skills Development for Peritoneal Dialysis Trainers. Issue 2 (March 2019) - Chow, Josephine S.F.; Cho, Yeoungjee; Equinox, Keri-Lu; Figueiredo, Ana; Frasca, Serena; Hawley, Carmel; Howard, Kirsten; Johnson, David W.; Jose, Matthew; Lee, Anna; Maley, Moira; Moodie, Jo-Anne; et al.
Background: Peritoneal dialysis (PD) is a home-based therapy where nurses train patients in its use. There has been no published randomized controlled trial (RCT) evaluating any specific protocol for nurses delivering PD training. A standardized education package based upon the best available evidence and utilizing modern educational practices may lead to improved patient outcomes. The aim is to develop a standardized, evidence-based curriculum for PD trainers and patients aligned with guidelines from the International Society for Peritoneal Dialysis (ISPD), using best practice pedagogy. Methods: A literature search and clinical audit were conducted to identify current practice patterns and best practice. Results were reviewed by a focus group of practitioners comprising PD nurses, nephrologists, consumers, a medical education expert, and an eLearning expert. From this, a training curriculum and modules were developed. Results: A comprehensive PD training curriculum has been developed, which includes modules for training PD nurses (trainers) and patient training manuals. The package comprises 2 introductory modules and 2 clinical case modules. The curriculum is designed for both interactive digital media (trainers) and traditional paper-based teaching with practical demonstrations (patients). Assessment is also addressed. Conclusion: The need for the development of a comprehensive and standardized curriculum for PD nurse trainers and their patients was confirmed. This paper outlines the process of the development of this curriculum. Pilot testing of the modules was launched in late 2017 to examine feasibility, and planning has commenced for a RCT in 2019 to investigate the effect of the modules on clinical outcomes, and their wider application across Australia and New Zealand.